When Is A Lineage A Species? A Case Study In Myxacorys gen. nov. (Synechococcales: Cyanobacteria) With The Description of Two New Species From The Americas. Issue 5 (24th August 2019) - Pietrasiak, Nicole; Osorio‐Santos, Karina; Shalygin, Sergei; Martin, Michael P.; Johansen, Jeffrey R.
Abstract : Soil cyanobacteria are crucial components of biological soil crusts and carry out many functions in dryland ecosystems. Despite this importance, their taxonomy and population genetics remain poorly known. We isolated 42 strains of simple filamentous cyanobacteria previously identified as Pseudophormidium hollerbachianum from 26 desert locations in the North and South America and characterized these strains using a total evidence approach, that is, using both morphological and molecular data to arrive at taxonomic decisions. Based on a phylogenetic analysis of 16S rRNA gene sequences, we propose and characterize Myxacorys gen. nov. with two new species Myxacorys chilensis, the generitype, and M .  californica . We also found distinct 16S‐23S ITS sequence variability within species in our dataset. Especially interesting was the presence of two distinct lineages of M. californica obtained from locations in close spatial proximity (within a few meters to kilometers from each other) suggesting niche differentiation. The detection of such unrecognized lineage‐level variability in soil cyanobacteria has important implications for biocrust restoration practices and conservation efforts.